Gynybai pritaikyti Vilniaus sakraliniai pastatai ir sakralinių pastatų ansambliai XIV-XVIII amžiuje - Girlevičius, Linas (Lietuvos istorijos studijos, 2008)
In the 14th-18th centuries, Vilnius had a number of sacral buildings adapted for defense purposes as well as ensembles of those buildings. This group of objects of the defense heritage is one of the components of the defense system of Vilnius. The analysis of the previous and the latest data has shown that the number of this kind of objects is much bigger than it has been assumed. Still, it is hypothetical whether some of them really belong to the group of defense heritage objects. A number of sacral buildings and their groups were established in places that were important in terms of the defense of Vilnius as early as in the 14th and 15th centuries. Relics of the early fortifications have remained in the territories of several sacral objects. The greater part of sacral buildings and monasteries discussed in the article were deliberately established in places that were important to the defense of the city and its environs, and quite a few were constructed by order of the ruler (Grand Duke of Lithuania and/or King of the Polish-Lithuanian State). In Vilnius, monasteries and nunneries were established according to the Christian traditions of constructing such ensembles of sacral buildings — they were built close to the border of the city of the time (14th-15th centuries) or in the peri-urban area. It is possible to trace the development of the early city and the strategy of its planning according to the locations of the monasteries suitable for defense purposes. Although the construction of Catholic and Orthodox churches and monasteries adapted for defense purposes was more typical of the 14th and 15th centuries, the tradition remained until the 18th century. A few of those buildings still have architectural fragments proving that they were meant to be defended with firearms. Thus, we can conclude that quite a number of the sacral monuments of Vilnius were ready to be used for defense purposes during battles. Monasteries were suitable for defense due to their planning — traditionally an enclosed ensemble of buildings. Yet, their role in the defense of the city was not very important, as they were only prepared for defense with light firearms. The further research of sacral buildings used for defense purposes is prospective and relevant when seeking to determine the defensive potential of Vilnius in the Middle Ages and the New Times. In the process of the research, the list of objects discussed in this article can be supplemented with new ones.